2004
DOI: 10.1029/2004eo480002
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying mineral dust mass budgets:Terminology, constraints, and current estimates

Abstract: Mineral dust aerosol is created by wind erosion of soil particles. In addition to its direct radiative effect, dust aerosol mediates ocean carbon uptake and the chemical cycles of other aerosols like sulfates. Dust observations during the past decade span measurements of local concentration and deposition to global satellite retrievals of aerosol optical thickness [Prospero et al., 2002]. Measurements of dust emission, whereby soil particles enter the atmosphere, are scarce. Because no single data set is suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
228
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(252 citation statements)
references
References 5 publications
8
228
2
3
Order By: Relevance
“…Land use such as agriculture can result in anthropogenic dust emissions, both through direct injection of dust particles during tillage, and through loss of soil cohesion leading to increased erosion rates (Zender et al, 2004). On a global scale, dusts emanating from agricultural sources are thought to represent a major contribution to anthropogenic dust emissions .…”
Section: O'sullivan Et Al: Ice Nucleation By Fertile Soil Dustsmentioning
confidence: 99%
“…Land use such as agriculture can result in anthropogenic dust emissions, both through direct injection of dust particles during tillage, and through loss of soil cohesion leading to increased erosion rates (Zender et al, 2004). On a global scale, dusts emanating from agricultural sources are thought to represent a major contribution to anthropogenic dust emissions .…”
Section: O'sullivan Et Al: Ice Nucleation By Fertile Soil Dustsmentioning
confidence: 99%
“…Dust particles are part of the coarse mode aerosol typically occurring in the super-µm size range (Haywood et al, 2001;Reid et al, 2003). Current estimates of annual global emission of dust particles that are available for long-range transport vary between 1000 and 2000 Tg (Zender et al, 2004).…”
Section: Wind-blown Dust and Climatementioning
confidence: 99%
“…Sahara is the more intense Aeolian dust source in the world and is responsible for half of the mineral dust emissions globally (Zender et al, 2004). Guerzoni et al (1999) and Kallos et al (2005) found that approximately 10 8 metric tons of dust are deposited annually over the Mediterranean Sea, and a similar amount is transferred towards Europe.…”
Section: Introductionmentioning
confidence: 99%